Interactive behaviors between mothers and their prematurely born infants in the face-to-face Still-Face Paradigm - Chiodelli, Taís (2020)
The present study compared and correlated interactive behaviors of 15 mothers and their very preterm infants (gestational age: 28-32 weeks). Mothers and infants were observed in the experimental Face-to-Face Still-Face paradigm, consisting of three episodes: in the first and third episodes (play and reunion episodes), mother and infant interact freely; in the second (still-face episode), the mother maintains a still-face expression. The behaviors of the infants were allocated in three categories: positive social orientation, negative social orientation and self-regulation. Maternal behaviors were classified into positive and negative social orientation. Intragroup comparisons indicated that maternal vocalizations were significantly higher in the play episode. Compared to other studies with preterm infants, babies in this study exhibit fewer interactive behaviors and more self-soothing behaviors in the still-face episode. In addition, in the reunion episode, values of the behaviors presented in the play episode were recovered. Correlations between intrusive maternal behaviors and noninteractive or negative-interaction behaviors of the infant suggest the relevance of providing intervention to promote maternal sensitivity.